Growth responses to elevated environmental humidity vary between phenological forms of Picea abies - Sellin, Arne; Heinsoo, Katrin; Kupper, Priit; Meier, Riho; Õunapuu-Pikas, Eele; Reinthal, Taavi; Rosenvald, Katrin; Tullus, Arvo (Frontiers in Forests and Global Change, 2024)
Introduction Global warming promotes geographical variability in climate, although the trends differ for the lower and higher latitudes of the Northern Hemisphere. By the end of the current century, the climate models project an increase of up to 20–30% in summer precipitation for northern Europe, accompanied by an increase in atmospheric humidity. Information on the effects of increasing precipitation and air humidity on the performance of northern trees is scant. Methods We studied the effects of artificially elevated air relative humidity (RH) and soil moisture on growth, phenology and needle/shoot morphology of 5-year-old Norway spruce (Picea abies) saplings at the Free Air Humidity Manipulation (FAHM) experimental site in eastern Estonia. The trees were subjected to three treatments: C – control, ambient conditions; H – air humidification, mean relative humidity + 5%; I – soil irrigation, precipitation +15%. Trees from pure stands were sampled from three experimental plots per treatment in 2022. Results The needle morphology of P. abies was insensitive to moderate changes in air humidity and soil water content in northern mesic conditions. In contrast, the humidity treatments significantly affected shoot size, which decreased in the following order: C > I > H. This finding indicates a certain deceleration of the development of trees’ assimilating surface under elevated air humidity. The humidity manipulation did not influence the timing of bud burst, but the trees differentiated between two phenological forms – early-and late-flushing forms. Trees growing under elevated RH exhibited slower growth rates compared to trees in C and I treatments. The early-flushing trees grew faster, while the late-flushing trees performed better under increasing environmental humidity. Conclusion At high latitudes, the increasing precipitation and concomitant rise in atmospheric humidity counteract the enhancement of trees’ growth and forest productivity predicted for boreal forests due to global warming. Given that the late phenological form of P. abies is more tolerant of wetter climates and less threatened by late spring frosts, it has a greater potential to adapt to regional climate trends predicted for northern Europe.